A multimodal simulation of on-demand transportation for a study on traffic congestion - Choo, Yaw Feng (Nanyang Technological University, 2020)
In recent years, overpopulation and overcrowding in Singapore has led to serious traffic delays and inconvenience. The poor traffic performance mainly caused by on the road vehicles congestion further increases the travelling time among road users specifically during peak hour, leading to longer, unpredictable and wastage of waiting time. In this report, the author summarizes the progress and key learning points of his Final Year Project, “A Multimodal Simulation of On-demand Transportation for a Study on Traffic Congestion” under the supervision of his instructor, Associate Professor Justin Dauwels. The author’s project focused on the study of implementation of the Personal Mobility Device (PMD) as an effort in reducing overcrowding and traffic congestion issues. PTV VISSIM software (multi-modal traffic flow simulation software) was utilized during the simulation to construct virtual and realistic real-life congestion situations to study the effect of PMD in serving as an alternative option for short distance travelling among road users. As such, Jurong East interchange together with its surrounding areas which is strategically located, was selected to be used as the layout model in this project. Different situations were being simulated to study the effects of the PMD which serves as one of the multimodal transport options for road users in alleviating the congestion problem in Singapore.